Heart rhythm characterisation during unexplained transient loss of consciousness in dogs. (September 2020) - Perego, M.; Porteiro Vàzquez, D.M.; Ramera, L.; Lombardo, S.F.; Pane, C.; Bontempi, L.V.; Santilli, R.A.
Highlights: Syncopal episodes are characterized by transient global cerebral hypoperfusion. Ventricular arrest typically results in transient loss of consciousness (TLOC) in dogs. TLOC in most dogs has the characteristics of a reflex or neurally-mediated syncope. Cardiac rhythm during the TLOC associated with a neurocardiogenic mechanism in 46.7% cases. Intrinsic rhythm disturbances of the sinus node or of the atrioventricular node in 31.5% cases. Electrocardiographic characterization of TLOC diagnostic, therapeutic, and prognostic plans. Abstract: The identification of the heart rhythm during an episode of transient loss of consciousness (TLOC) is considered the reference standard method to elucidate the underlying aetiology. This study aimed to characterise heart rhythm in dogs during TLOC using Holter and external loop recorder monitoring. We retrospectively reviewed 24-h Holter monitoring and external loop recorder tracings from 8084 dogs. Heart rhythms from dogs that experienced TLOC during the recording was analysed to identify rhythm disturbances that occurred during episodes of TLOC. Electrocardiograms (ECGs) were subsequently categorised into Type 1 (ventricular arrest), Type 2 (sinus bradycardia), Type 3 (no/slight rhythm variations), and Type 4 (tachycardia). Transient LOC was documented in 92 dogs over 230 episodes of TLOC. Percentage of cases with ECGs compatible with each classification were as follows: 72.1%, Type 1; 6.1%, Type 2; 20.9%, Type 3; and 0.9%, Type 4. Cardiac rhythm during the TLOC could have been a consequence of a neurocardiogenic mechanism in 46.7% cases, while intrinsic rhythm disturbances of the sinus node or of the atrioventricular node were diagnosed in 31.5% cases. In two cases, tachycardia was the possible cause of the TLOC. ECG patterns in dogs presenting with multiple TLOC episodes were completely reproducible during each episode. TLOC in dogs was primarily caused by ventricular arrest. Most dogs with TLOC had electrocardiographic finding suggestive of a reflex or neurally-mediated syncope, but one third had an ECG more suggestive of a conduction disorder. Distinguishing these two entities could help inform diagnostic, therapeutic, and prognostic plans.